Entecavir administration to pregnant Japanese woman with chronic hepatitis B and hepatocellular carcinoma: A case report. Issue 3 (16th February 2021) - Kakiuchi, Toshihiko; Takahashi, Hirokazu; Iwane, Shinji; Koji, Azusa; Matsuo, Muneaki
Abstract: Women taking entecavir hydrate (ETV) may not need to consider abortion in the event of an unexpected pregnancy. If a woman with renal dysfunction and taking ETV for chronic hepatitis B becomes pregnant, continuous use of ETV may also be tolerated. Abstract : For pregnant women taking entecavir hydrate (ETV) with renal dysfunction for chronic hepatitis B, continuous use of ETV may also be tolerated. In this case, the child's height and body weight were in the normal ranges during the long term.